Meta-Analysis of Adiponectin as a Biomarker for the Detection of Metabolic Syndrome - Liu, Zhengtao; Liang, Shuheng; Que, Shuping; Zhou, Lin; Zheng, Shusen; Mardinoglu, Adil (Frontiers in Physiology, 2018)
Previous studies revealed the potential significance of circulating adiponectin levels with respect to the diagnosis and prediction of metabolic syndrome, but uncertainty has been noted across different cohorts. Systematic evaluation was performed for diagnostic accuracy and predictivity of adiponectin variation for metabolic syndrome in enrolled studies including 1248 and 6020 subjects, respectively. Adiponectin can identify metabolic syndrome with moderate accuracy (area under the curve=0.81, 95% CI: 0.77-0.84). Heterogeneity analysis revealed that an increasing index of insulin resistance was independently associated with improving the performance of adiponectin upon metabolic syndrome diagnosis (ratio of diagnostic odds ratio=3.89, 95% CI: 1.13-13.9). In addition, reductions in adiponectin were associated with increasing metabolic syndrome incidence in a linear dose-response manner. The risk of hypoadiponectinemia with metabolic syndrome was especially increased in men (P<0.05). Further Mendelian randomization analysis identified that the amplified risk could be attributed to increased susceptibility (up to 7%) to insulin resistance compared with women. In conclusion, adiponectin measurement might have potential benefits in the detection of metabolic syndrome. Factors that affect insulin resistance should be considered for adjustment in future assessments.